HOME BASED PULMONARY REHABILITATION IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE: CASE STUDY - Liliana Silva; Bruno Delgado (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Pulmonary Rehabilitation is the non-pharmacological treatment indicated for people with COPD, with physical exercise and health education focused on the development of self-care and self-management, promoting physical, emotional condition, adherence to the therapeutic regime and quality of life. It is intended to demonstrate the effectiveness of a home PR program. Method: Quantitative case study that took place over 8 weeks, with biweekly multidisciplinary intervention, using exercise training, education sessions and telephone follow-up. Functional assessment was performed at admission and discharge, using the instruments Clinical CCQ Questionnaire, Sit and Stand Test (T S&L) and Barthel Index. Results: A 70-year-old man, diagnosed with COPD, performed 16 face-to-face training sessions as planned. It presented significant functional evolution: initial CCQ 4.5, final 3.2; T S&L initial 5, final 14; Initial Barthel index 55, final 90. Conclusion: The outlined pulmonary rehabilitation program demonstrated effectiveness and safety, promoting significant functional improvement.